Sie sind auf Seite 1von 2

n 2

x i−μ
1) X =∑ 2

i=1
( )
σ

a11 a12 a 13 x 1 b1
2)
( a21 a22 a 23 x 2 = b2
a31 a32 a 33 x 3 b3 )( ) ( )
5+ √ 25−4 p
3)
{ 2p
5−√ 25−4 p
2p
∧¿ 0

∧¿ 0

−b ± √ b2−4 ac
4) x 1,2=
2a

m n
−1
5) S=∑ S j ( 1+ pt j /K ) + ∑ S j ( 1+ pt j / K )
j=1 j=m +1

6)

12

( log 1,5
12
−3−x
=log 1,5 (1−x ) ⇔ −3−x
=1−x ,
)
−3−x> 0 ,
1−x >0 , ({

−12=3−2 x−x 2 ,
3+ x< 0 ,
1> x ,

) ({
x 2+ 2 x−15=0 ,
x ←3 ,
x <1 ,
⇔ x=
) ({ ) ({
ln cos x x 2−2 x +1 sin x 1−cos x
7) a) lim ; b) ) lim ; c) ) lim ; d) lim ;
n→∞ ln cos 3 x n→∞
2
x −1 n → ∞ cos x−1 n → ∞ x ( √ 1+ x−1 )

xdx
8) a) ∫ arctgxdx , b)∫ , c) ∫ cos x cos 5 xdx.
√ 3−x 4
1 2 4
9)
|−1 3 7
4 −2 6 |
2 7 3

[
10) A= 3 −12 4
1 3 3 ]

Das könnte Ihnen auch gefallen